2023
DOI: 10.3390/su151310616
|View full text |Cite
|
Sign up to set email alerts
|

Urban Growth Management in Riyadh, Saudi Arabia: An Assessment of Technical Policy Instruments and Institutional Practices

Abstract: This paper assesses the effectiveness of technical policy instruments used to manage urban growth and examines their relationship with institutional practices in the city of Riyadh, Saudi Arabia. A quantitative method by means of a questionnaire was adopted to examine research questions, while a qualitative method was used to better understand technical policy instruments and their relationship with institutional practices. Findings reveal that technical policy instruments are unable to manage urban growth eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Aldegheishem [87], Aldegheishem [88], Alamoudi et al [89] found empirically that the progress of smart sustainable cities in Saudi Arabia is related closely to the level of citizens' participation in decision making process. As a result, managing sustainable urbanization in Al-Madinah has witnessed several positive transformations.…”
Section: Performance Of Sdg 11mentioning
confidence: 99%
“…Aldegheishem [87], Aldegheishem [88], Alamoudi et al [89] found empirically that the progress of smart sustainable cities in Saudi Arabia is related closely to the level of citizens' participation in decision making process. As a result, managing sustainable urbanization in Al-Madinah has witnessed several positive transformations.…”
Section: Performance Of Sdg 11mentioning
confidence: 99%